Aid understood (2) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Understanding European Community aid - aid policies, management and distribution explained by Aidan Cox and Antonique Koning 1997 119pp ISBN 0 85003 396 9